Paroki menurut Hukum Gereja - Joko, Antonius Padua Dwi (Lux et Sal, 2023)
The term "parish" refers to a part of a diocese. According to the 1983 Code of Canon Law (CIC) canon 515, a parish is composed of the following essential elements for its existence: a congregation of Christian faithful, a place of worship where Christians can gather or be found, a territory or area, and a pastor responsible for the parish. Although parishes are generally territorial in nature, if it is considered beneficial, personal parishes may be established, which are determined on the basis of rite, language, nation of the Christian faithful of a particular territory, and also on other grounds (canon 518). In modern times, parishes no longer emphasize territorial areas, but rather emphasize parishes as the Church, the People of God.